Growth Response, Physiology, Metabolomic, and Production of Micro-Tom Tomatoes to Additional Lighting with White and Purple Light-Emitting Diode - Lubis, Wahyu Muhammad Yuha; Hapsari, Dhika Prita; Poerwanto, Roedhy; Matra, Deden Derajat (Department of Agronomy and Horticulture, IPB University, 2025)
Tomatoes are a widely produced and consumed fruit-vegetable belonging to the Solanaceae family. It contains minerals, vitamins, essential amino acids, sugars, and fiber. Micro-Tom is a wild-type cultivar from a cross between the Florida Basket and Ohio 4013-3 cultivars. Micro-Tom has two mutant types, the iaa9-3 and iaa9-5 mutants, which exhibit strong parthenocarpic properties. It is classified as a mutant tomato due to a mutation in the IAA9 gene, which belongs to the Auxin/IAA (Indole-3-Acetic-Acid) gene family and plays a role in suppressing the endogenous auxin signal transcription pathway. Using artificial light in cultivation techniques shortens the plant cycle and accelerates the juvenile phase. This study aimed to investigate the morphological, physiological, and production responses of Micro-Tom tomatoes to supplemental LED lighting. The research was conducted at the Leuwikopo experimental field of IPB University from March to November 2023. A completely randomized design was employed, with two factors (LED spectrum and Micro-Tom genotyping) and nine replicates. The study also examined the potential benefits of combining polychromatic and monochromatic light-emitting diodes (LEDs). The response of Micro-Tom tomatoes to artificial lighting with purple and white LEDs did not show significant differences in growth and production parameters. However, significant differences were observed between the tomato types, specifically between the Wild-type and the iaa9-3 mutant. No significant differences were found in LED treatment or Micro-Tom genotype for physiological parameters such as chlorophyll content and glucose-fructose levels. Regarding fruit quality, no significant differences were observed for parameters such as total soluble solids (TSS, Brix) to total titratable acidity (TTA, acidity), glucose and fructose, and malic acid. The LC-MS/MS analysis of leaves exposed to purple LED light revealed a profile dominated by secondary metabolites from the fatty acid compound group, suggesting the potential benefits of this lighting combination. In conclusion, using LED lights can accelerate the plant life cycle and shorten the juvenile phase, as evidenced by the first flower emergence, which occurred 20 days after transplanting (DAT) in the wild-type genotype and 16 DAT in the mutant genotype.